The role of al-Istiqlal university in promoting the positive values and trends of the work and conduct of the members of the Palestinian security establishment in the west bank - Wan Mohd Yusof, Wan Chik; Mohamed Yusouf, El-Kirem; Sameer Suleiman, Al-Jamal
The study aimed to identify the role of Istiqlal University in promoting the positive values and trends of the work and behavior of the Palestinian security institution in the West Bank from the point of view of graduate students working in the security establishment. According to variables: (governorate, social status, Rank).The study followed the descriptive analytical approach. The study population is (808). A questionnaire consisting of (18) paragraphs was used. The study sample size (132) was (16.34%). The results of the study indicated a positive role for Istiqlal University in promoting positive values and trends such as promoting discipline, commitment, respect for the rule of law and respect for human rights. The absence of statistically significant differences in the responses of the respondents on the role of Istiqlal University in promoting positive values and trends of the work and behavior of the members of the Palestinian security institution in the West Bank due to the variables of social status governorate, Rank. The study produced a number of recommendations, the most important of which are: attention through education to instill values and positive attitudes among students, preparation of studies and visions on ways of integrating roles between the university and the security establishment. Between Istiqlal University and all faculties, institutes and schools of security training affiliated to the Palestinian security establishment, conduct research related to how to strengthen the national ownership of security education and training.